The problems of economic growth in Ukraine: reasons of constraints and their solution - Antoniuk, V.; Mytsenko, I.; Aнтонюк, В.; Миценко, І. (My University, 2019)
The most important problem in the development of Ukraine is the slow pace of economic growth, which causes it to lag behind the developed countries and the low level of welfare of the population. It is important for Ukraine to search for and actively use modern growth factors. The purpose of the article is to analyse the reasons for limiting the growth rate of the Ukrainian economy in the context of modern growth theories and to identify ways to overcome them.
Проблеми економічного росту в Україні: причини стримування і їх рішення
Keywords: economic growth; theory of endogenous growth; investments; human capital; structure of economy; industry